The effectiveness of a training program based on the Higashi method in developing social interaction among children with autism disorders - et. al., Dr. Khaled Ahmad Obeidat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Introduction: Children with autism spectrum disorder suffer from problems in social interaction skills, which leads to their isolation and inability to integrate into society and the surrounding environment. Therefore, the study aimed to prepare a training program based on the Higashi method in developing social interaction skills for children with autism spectrum disorder. And verify its effectiveness in the measurements, pre-test, post-test and delayedtest . Methodology: The study used the semi-experimental approach by adopting quantitative design. To achieve the objectives of the study, the scale of social interaction skills was used.And it consisted of 15 children, experimental and consisting of 15 children, and the scale was applied to them, and appropriate statistical analyzes were performed. The quantitative results were extracted through the multiple analysis of variance test, the accompanying analysis of variance test, and the single analysis of variance test. Results: The results showed the effectiveness of the training program through the development of social interaction skills. The results also resulted in the existence of statistically significant differences at the level of significance (a = 0.05) between the mean scores of the members of the control and experimental groups in the pre-test and post-test on the scale of social interaction skills, and also indicated that there were no statistically significant differences at the level of significance (a = 0.05). Among the mean scores of the experimental group members in the post-test and delayed-test on the scale of social interaction skills:The study contributes to the integration of children with autism spectrum disorder through the development of social interaction skills, activating the role of families and their involvement in developing the necessary programs for their children, and training specialists on how to prepare training and extension training programs and early intervention programs that help these children in developing the life skills necessary for their integration into society And to stay away from isolation and introversion.